2013
DOI: 10.1136/thoraxjnl-2013-204457.97
|View full text |Cite
|
Sign up to set email alerts
|

S90 Effectiveness of Voriconazole In the Treatment of Aspergillus fumigatus Associated Asthma

Abstract: compared to the least (MRC 2 and 3) (HR 0.40, p = 0.023). Conclusion These data show that COPD patients who receive acute NIV have high risk of hospital readmission including requirement for repeat NIV treatment, which contributed to a significant number of hospital bed days. Although overall outcomes are better than previously reported (Murray, Thorax 2011), patients with high levels of premorbid dyspnoea have the highest mortality following acute hypercapnic exacerbations of COPD requiring NIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…We did not assess the effect of treatment on airway mycosis; nevertheless we assume that treatment reduced fungal burden especially in those patients who stopped producing sputum during the course of antifungal therapy. The study by Agbetile, et al [23], that reported that voriconazole was ineffective in treating asthma included many smokers; their burden of intractable non-asthmarelated airway obstruction may have obscured actions of any drug that simply reduced fungal burden and its associated inflammation, thereby explaining the difference between their study and ours. Studies of anti-fungal therapy in allergic bronchopulmonary aspergillosis (ABPA) suggested that an important effect of anti-fungal agents such as itraconazole in such infections is to reduce production of allergens and other molecules that promote the immunologic and inflammatory responses that result in asthma [33].…”
Section: Benefits Of Antifungal Therapy In Asthma Patientsmentioning
confidence: 58%
See 3 more Smart Citations
“…We did not assess the effect of treatment on airway mycosis; nevertheless we assume that treatment reduced fungal burden especially in those patients who stopped producing sputum during the course of antifungal therapy. The study by Agbetile, et al [23], that reported that voriconazole was ineffective in treating asthma included many smokers; their burden of intractable non-asthmarelated airway obstruction may have obscured actions of any drug that simply reduced fungal burden and its associated inflammation, thereby explaining the difference between their study and ours. Studies of anti-fungal therapy in allergic bronchopulmonary aspergillosis (ABPA) suggested that an important effect of anti-fungal agents such as itraconazole in such infections is to reduce production of allergens and other molecules that promote the immunologic and inflammatory responses that result in asthma [33].…”
Section: Benefits Of Antifungal Therapy In Asthma Patientsmentioning
confidence: 58%
“…Although fungal infections have been implicated pathophysiologically in diverse allergic airway diseases [18,20,26,31,32], treatment with antifungals has not been unequivocally beneficial. Treatment with itraconazole reportedly improved asthma symptoms [22] prompting sporadic use of antifungals in others with positive fungal cultures [20][21][22]25], but the lack of efficacy of voriconazole in asthmatics [23] called to question the value of these agents and prompted us to evaluate outcomes of similar asthmatics treated with antifungals in our clinic. The results of our analysis support the notion that antifungal treatment, especially with voriconazole, results in symptomatic improvement in some adult asthmatics with moderate to severe disease.…”
Section: Benefits Of Antifungal Therapy In Asthma Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…[146][147][148][149][150][151][152][153] The lower serum levels reduce but do not eliminate the risk of drug interactions and other side-effects. 155 Fungal sensitization in children may be associated with a more severe phenotype, 156 but there are no randomized controlled trials of treatment. 3.…”
Section: Invasive Testingmentioning
confidence: 99%